Optimizing human memory: an insight from the study of al Huffaz - Dzulkifli, Mariam Adawiah; Abdul Rahman, Abdul Wahab; Badi, Jamal Ahmed Bashier; Solihu, Abdul Kabir Hussain; Afzal, Sofia (IEEE, 2014)
We investigated the memory control processes used by a group of people who commit to memory the entire word text of the Quran with complete accuracy. The findings from interviews conducted, strengthened the involvement of several control processes such as rehearsal, motivation or interest and self-discipline. More importantly,it has been found that it is maintenance and not elaborative rehearsal that plays the most important role in the memorization of the Quran. These findings will help to form a better understanding o f the cognitive basis underlying human memory. This knowledge can be incorporated with technology for the purpose of optimizing human potential. More importantly, it gives implications to learning process at large and opens new opportunities and ways to serve the Ummah better.